Boiled ginger and honey intervention for hyperemesis gravidarum - Nursyahid Siregar; Ega Ersya Urnia; Jasmawati Jasmawati; Irma Mustika Ningsih; Rahmawati Wahyuni; Rosalin Ariefah Putri; Dewi Rinda Astuti; Heni Suryani; Elisa Goretti Sinaga (Intelektual Pustaka Media Utama, 2026)
Hyperemesis gravidarum is excessive vomiting which can cause dehydration, lack of carbohydrate and fat reserves in the body, and Mallary Weiss syndrome due to gastrointestinal bleeding. Boiled ginger and honey were administered as an initial complementary treatment to reduce nausea and vomiting in pregnant women with hyperemesis gravidarum. This study aims to determine the effect of giving ginger and honey decoction on the frequency of hyperemesis gravidarum in pregnant women. This study employed a quasi-experimental design with a one-group pretest-posttest approach. The population was all pregnant women who experienced nausea and vomiting, outpatients, and inpatients at Inche Abdoel Moeis Hospital. The sample consisted of 18 people using consecutive sampling technique. The severity of nausea and vomiting was measured using the pregnancy-unique quantification of emesis and nausea (PUQE) questionnaire. Statistical analysis was performed using the Wilcoxon signed-rank test to compare pretest and posttest scores. The Wilcoxon Test results obtained a significance value of 0.000 < 0.05. There is an effect of giving ginger and honey decoction on the frequency of hyperemesis gravidarum. Pregnant women are advised to use a decoction of ginger and honey, apart from that, other researchers are advised to use a control group in subsequent studies.